2007
DOI: 10.1080/00050060701280607
|View full text |Cite
|
Sign up to set email alerts
|

Why promoting biological ideology increases prejudice against people labelled “schizophrenic”

Abstract: Although the public understands that many factors influence who ends up crazy, terrified or miserable, studies consistently find that they place much more emphasis on adverse life events than on chemical imbalances or genetics. Biological psychiatry, enthusiastically supported by the pharmaceutical industry, insists on trying to educate the public that they are wrong. This ''mental illness is an illness like any other'' approach to destigmatisation ignores the large body of research evidence that biogenetic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 109 publications
4
84
2
Order By: Relevance
“…For example, previous research has shown that biological beliefs about schizophrenia tend to predict stigmatizing attitudes such as social distancing, but the same is not true for depression (Dietrich et al, 2004;Goldstein & Rosselli, 2003;Read, 2007). The varying effect of biological explanations on different behaviors is consistent with essentialism.…”
Section: Reasons For the Varied Effect Of Biological Explanationsmentioning
confidence: 51%
See 1 more Smart Citation
“…For example, previous research has shown that biological beliefs about schizophrenia tend to predict stigmatizing attitudes such as social distancing, but the same is not true for depression (Dietrich et al, 2004;Goldstein & Rosselli, 2003;Read, 2007). The varying effect of biological explanations on different behaviors is consistent with essentialism.…”
Section: Reasons For the Varied Effect Of Biological Explanationsmentioning
confidence: 51%
“…associated with favorable or unfavorable attitudes toward stigmatized groups (Haslam, Rothschild, & Ernst, 2002;Hegarty, 2002;Jayaratne et al, 2006;Read, 2007;Verkuyten, 2003). Furthermore, individuals can use the same biological information to support favorable or unfavorable views toward stigmatized social groups (Boysen & Vogel, 2007;Shelton, Pfeffer, Jayaratne, Feldbaum, & Petty, 2007).…”
mentioning
confidence: 94%
“…It can also exacerbate the perception that mental disorders are relatively permanent and difficult to overcome or treat effectively, which is known as prognostic pessimism (9,13,23). Additionally, if the behavior of people with psychiatric disorders is seen as deterministically governed by biological abnormalities outside of their control, they may be seen as unpredictable, contributing to perceptions of them as dangerous, fearsome, and meriting avoidance (22,24,25). Moreover, viewing the actions of people with psychiatric illnesses as caused by neural or genetic aberrations-rather than by their own agency (23)-might trigger mechanistic dehumanization, which occurs when people are equated to automata or systems of interacting parts and is strongly linked to negative attitudes (20).…”
mentioning
confidence: 99%
“…For example, biological explanations appear to lead to certain forms of so-called psychological essentialism (specifically, genetic essentialism and neuroessentialism) in which mental disorders are seen as having unique, immutable essenceslocated in the brain or DNA-that produce the symptoms and behavior of patients (13,19). This view, in turn, can yield the belief that people with mental disorders are categorically dissimilar from so-called normal people, and the perception of such strict social boundaries between groups of people can lead to more negative intergroup attitudes (13,(20)(21)(22). It can also exacerbate the perception that mental disorders are relatively permanent and difficult to overcome or treat effectively, which is known as prognostic pessimism (9,13,23).…”
mentioning
confidence: 99%
“…The history of the treatment of drug addiction and other psychiatric disorders suggests that we should be sceptical about both these claims [86]. Neuroscience has yet to increase the use of treatment, and in the case of other psychiatric disorders, decrease stigma and discrimination [87].…”
Section: Implications For Behavioural Addictionsmentioning
confidence: 99%